2006
DOI: 10.1111/j.1471-1842.2006.00635.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical effectiveness and allied health professionals: an information needs assessment

Abstract: Objective: To determine the information needs and support required by AHPs whilst building services based on clinical effectiveness. Methods: A qualitative approach using action research in co-operation with a Rehabilitation Department Clinical Effectiveness group, leading to interviews with eight therapists. The sampling strategy was purposive. Results: Therapists have well-developed professional networks, but are unsure how to access traditional library areas. Library training can stop AHPs in asking for hel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…The participants in the research reported here perceive library and information services as the key to a rather uncertain professional environment and future for community pharmacists in Greece. However, the problems mainly considered to be significant by community pharmacists for accessing information services are also a common finding in other studies for health care professionals 37 and include the lack of time and lack of organized facilities such as libraries and information services. The development of specialized library and information services, as well as continuing education, will decrease the gap in the scientific knowledge and help pharmacists to further explore their opportunities to assume a novel and a unique role among health care professionals.…”
Section: Discussionmentioning
confidence: 97%
“…The participants in the research reported here perceive library and information services as the key to a rather uncertain professional environment and future for community pharmacists in Greece. However, the problems mainly considered to be significant by community pharmacists for accessing information services are also a common finding in other studies for health care professionals 37 and include the lack of time and lack of organized facilities such as libraries and information services. The development of specialized library and information services, as well as continuing education, will decrease the gap in the scientific knowledge and help pharmacists to further explore their opportunities to assume a novel and a unique role among health care professionals.…”
Section: Discussionmentioning
confidence: 97%
“…What they did not anticipate was discovering the extent to which respondents wanted to increase their professional, collaborative interactions with the librarians. Projects reported by Haigh [16] and Klein-Fedyshin et al [17] offer examples of the value of this type of multidisciplinary collaboration. However, as Lyon et al [18] concluded in their study of collaborations in bioinformatics work, librarian visibility is critical to identifying and building productive collaborative projects.…”
Section: Discussionmentioning
confidence: 99%
“…Because needs assessments focused on the training requirements of persons in multiple organizations generally involve a variety of methods to collect information (Chan et al, 2003;Gould, Kelly, White, & Chidgey, 2004;Haigh, 2006;Ringstad, Skaarup, Henriksen, & Davis, 2006), several procedures were used to collect data for this needs assessment of DELTA and RPE practitioners. Document reviews were used to collect information concerning the characteristics of the DELTA and RPE practitioners and the characteristics of the agencies that house these programs.…”
Section: Methodsmentioning
confidence: 99%